The Big Five, happiness, and shopping. (July 2016) - Goldsmith, Ronald
Abstract: This study assessed the relationships between the Big Five dimensions of personality and individual happiness with three indicators of shopping and spending for non-grocery items using a sample of 660 U.S. adults. The data from an online survey showed that all five of the Big Five traits correlated positively with self-reported happiness, even controlling for the effects of age and gender. Regression analysis showed, however, that the positive relationships between happiness and Agreeableness and Openness to Experience were no longer significant, indicating that they are real, but redundant to the other traits. The correlations also showed that happiness, Openness to Experience, and Extraversion correlated positively with the three shopping indicators. Finally, happiness appears to have a direct effect with shopping and mediates the influence of Emotional Stability, Agreeableness, and Extraversion on happiness.